Perceived Social Exclusion during the COVID-19 Pandemic: a European Perspective - Marina Zannella; Elena Ambrosetti; James Rhys Edwards (Social Indicators Research, 2026)
This paper aims to study the self-perceived social exclusion of EU citizens during the COVID-19 emergency, taking into account their socio-demographic characteristics and the specific contexts of their countries of residence. To this end, we draw on data from the third round of the electronic Eurofund Living, working and COVID-19 survey , conducted between February and March 2021, when countries were still grappling with various levels of lockdown and individuals had been living with COVID-19 restrictions for almost a year. We also rely on data from the Oxford COVID-19 Government Response Tracker (OxCGRT), which collected real-time information on government responses to COVID-19 in several countries during the pandemic crisis. We assume that during the pandemic, government accountability and responsiveness were important determinants of social inclusion and well-being. To test our hypothesis, we use multilevel logistic regression. Our dependent variable is a binary indicator of social exclusion. At the country level, we consider two different sets of explanatory variables concerning, respectively, subjective (i.e., citizens' perceptions) and objective (i.e., measures taken) aspects of governments' responses to COVID-19. Our results document a different gradient of social vulnerability across population groups. Our findings also indicate that social exclusion strongly depended on the country context, in addition to individual characteristics and circumstances. Collective perceptions of the efficiency of government responses and levels of trust in government had a positive association with the decrease in the feelings of social exclusion during the first year of the pandemic. Conversely, the objective measures implemented by national governments to mitigate socio-economic and health consequences were not associated with self-reported experiences of social exclusion.
Keywords: 300; COVID-19; Social exclusion; Well-being; Europe; Public health; Institutional trust